Metacognitive Writing Strategies of Master Students in the Departments of English at Yemeni Universities - Saleh, Nasr Mohsen Ali; Mutahar, Abbas Abdul-Malik Mohammed; Alwai, Abdullah Mohammed Salem (International Journal of Language and Literary Studies, 2025)
This study investigates the use of metacognitive writing strategies among master's students in the English departments at Yemeni universities, focusing on their role in enhancing academic writing proficiency. Using a quantitative descriptive design, data were collected from 30 master’s students at Sana’a and Aden universities through a validated questionnaire. The findings reveal that while students demonstrate strong awareness of metacognitive strategies in planning, monitoring, and evaluating their work, they face challenges in applying advanced cohesive devices such as ellipsis, substitution, and collocations. Gender and specialization were found to have no significant impact on the use of these strategies. The study recommends the need for targeted interventions to address these challenges, emphasizing reflective practices, structured training, and the integration of digital tools to foster self-regulation and continuous improvement. These findings contribute to the growing literature on metacognitive strategies and offer practical insights for educators and policymakers in higher education.